Individual Characteristics in the Comprehension of Pandemic Video Communication: Randomized Controlled Between-Subjects Design - Lungu, Daniel Adrian; Røislien, Jo; Smeets, Ionica; Wiig, Siri; Brønnick, Kolbjørn Kallesten (Journal of medical Internet research, 2024)
Video played an important role in health communication throughout the COVID-19 pandemic. It was used to communicate pandemic information to the public, with a variety of formats, presenters, and topics. Evidence regarding the effectiveness of video features is available, while how individual characteristics of recipients influence communication comprehension is still limited. This study aimed to test 6 individual characteristics and assess their effect on the comprehension of pandemic video communication. Short health communication videos were presented to a large sample of subjects, receiving questionnaire responses from 1194 participants. Individual characteristics consisted of age, sex, living area, education level, income level, and belief in science. Communication comprehension consisted of both perceived and objective comprehension. The data were analyzed by multiple linear regression. Age had a negative effect on both perceived and objective comprehension-age was negatively associated with comprehension. There were sex differences, with higher perceived comprehension and lower objective comprehension among female than male individuals. Living in an urban or a rural area had no significant effect (all P>.05). The level of education and income had a positive effect on both subjective and objective comprehension. Finally, the belief in science had a positive effect on perceived comprehension (P<.001) but did not have a statistically significant effect on objective comprehension (P=.87). The main differences between those who think they understand pandemic communication and those who comprehend it better are sex (female individuals have a higher perception of having comprehended, while male individuals have higher levels of objective comprehension) and belief in science (higher belief in science leads to higher perceived comprehension, while it does not have any impact on objectively understanding the message conveyed).